1991
DOI: 10.1046/j.1537-2995.1991.31391165172.x
|View full text |Cite
|
Sign up to set email alerts
|

Commentary on the safety of red cells preserved in extended‐storage media for neonatal transfusions

Abstract: Red cells preserved in extended-storage media are the standard product dispensed by many regional blood centers. When the red cells are intended for neonatal transfusion, concern exists about the safety of the relatively high quantities of additives present in these media. Definitive studies to address these concerns are not available. Therefore, to estimate the effects of additives and to delineate circumstances in which they might be harmful, the quantities transfused in defined clinical settings were calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(59 citation statements)
references
References 13 publications
0
58
0
1
Order By: Relevance
“…Blood banking strategies designed to accommodate the needs of the small infant have addressed problems related to handling of small blood volumes, limiting donor exposure, and minimizing blood wastage (30)(31)(32)(33)(34). Holland et al (35) have suggested that delayed clamping of the umbilical cord decreases transfusion requirements during the first week of life.…”
Section: Discussionmentioning
confidence: 99%
“…Blood banking strategies designed to accommodate the needs of the small infant have addressed problems related to handling of small blood volumes, limiting donor exposure, and minimizing blood wastage (30)(31)(32)(33)(34). Holland et al (35) have suggested that delayed clamping of the umbilical cord decreases transfusion requirements during the first week of life.…”
Section: Discussionmentioning
confidence: 99%
“…There are theoretical concerns over potential toxicity of adenine and mannitol if given in large volumes to neonates [3], but a randomized trial showed apparent safety of these additives in neonatal cardiac surgery [4], and they are widely used for neonatal cardiac surgery in the UK with no evidence of adverse effects. Several retrospective studies have also reported an association between red blood transfusions and subsequent necrotizing enterocolitis (NEC) in neonates [5,6], but proof of a causal association requires prospective studies.…”
Section: Recognized Hazards Of Transfusion In Neonatesmentioning
confidence: 99%
“…The RBC units stored in citrate-phosphate dixtrose-adenine (CPDA) solution with hematocrit 60-70% or in additive solution like saline -adenine-glucose mannital (SAGM) with hematocrit of about 50-60% are safe and efficacious for small volume transfusions. 8 It is also established that transfusing stored, rather than fresh red cell units present no risks when used for small volume transfusion as regard to potassium level, red cell 2, 3 diphosphoglycerate or other constituents present in additive solutions. 9 However, after 5 days of storage, the plasma potassium content is substantially elevated, so < 5 day-old blood should be used in case of rapid and large-volume transfusions.…”
Section: Selection Of Red Cell Componentsmentioning
confidence: 99%